Comparing different intestinal contrast agents in multislice computed tomography enterography examination for Crohn’s disease - Li Jiayan; Zhang Junmei; Cao Di (结直肠肛门外科)
[Objectives] To compare different intestinal contrast agents in multislice computed tomography enterography (MSCTE) examination for Crohn’s disease (CD). [Methods] Sixty patients requiring MSCTE examination for a diagnosis of CD at Beijing Anorectal Hospital—Beijing Erlong Road Hospital from January 2018 to December 2019 were recruited and randomly assigned to receive lactulose (n=30) or mannitol (n=30) as the contrast agents. The followings were compared between the two groups: imaging effect evaluated using the cross-sectional diameter of the small intestinal canal (duodenum, jejunum, and ileum), degree of small intestinal dilatation, and clarity of display of intestinal wall structures, distinctive imaging characteristics of MSCTE examination in patients with CD, adverse effects (AE), and score of acceptance of intestinal contrast agents. [Results] The two groups did not differ significantly in terms of the cross-sectional diameter of the small intestinal canal (duodenum, jejunum, and ileum), degree of small intestinal dilatation, clarity of display of intestinal wall structures, and distinctive imaging characteristics of MSCTE examination of CD (P>0.05). Within 24 hours of oral administration, in the lactulose group, six patients experienced one AE, two patients experienced two AEs, and no patient experienced three AEs; in the mannitol group, six patients experienced one AE, two patients experienced two AEs, and two patients experienced three AEs. No patient had AEs such as electrolyte disturbance, dehydration, and palpitations. The overall AEs rate was significantly lower, and the score of acceptance of intestinal contrast agent was significantly higher in the lactulose group than in the mannitol group (P<0.05). [Conclusion] Compared with traditional contrast agent of mannitol, lactulose can achieve comparable effect with fewer AEs. Its other advantages include better taste, better acceptance, and the potential to protect intestinal tract; therefore, it may be more suitable for CD patients.